Genetic characteristics and treatment outcome in infants with KMT2A germline B‐cell precursor acute lymphoblastic leukemia: Results of MLL‐Baby protocol. Issue 4 (30th January 2023) - Popov, Alexander; Tsaur, Grigory; Permikin, Zhan; Henze, Guenter; Verzhbitskaya, Tatiana; Plekhanova, Olga; Nokhrina, Ekaterina; Valochnik, Alena; Sibiryakov, Petr; Zerkalenkova, Elena; Olshanskaya, Yulia; Gindina, Tatiana; et al.
Abstract: The aim of this study was to present the diagnostic and outcome characteristics of infants with germline status of KMT2A gene ( KMT2A ‐g) B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL) treated consistently according to the MLL‐Baby protocol, a moderate‐intensity protocol. Of the 139 patients enrolled in the MLL‐Baby study, 100 (71.9%) carried different types of rearranged KMT2A ( KMT2A ‐r), while the remaining 39 infants (28.1%) had KMT2A ‐g. KMT2A ‐g patients were generally older (77% older than 6 months), less likely to have a very high white blood cell count (greater than 100 × 10 9 /L), less likely to be central nervous system (CNS)‐positive, and more likely to be CD10‐positive. The 6‐year event‐free survival and overall survival rates for all 39 patients were 0.74 (standard error [SE] 0.07) and 0.80 (SE 0.07), respectively. Relapse was the most common adverse event ( n  = 5), with a cumulative incidence of relapse (CIR) of 0.13 (SE 0.06), while the incidence of a second malignancy ( n  = 1) and death in remission ( n  = 3) was 0.03 (SE 0.04) and 0.08 (SE 0.04), respectively. None of the initial parameters, including genetics and the presence of recently described fusions of NUTM1 and PAX5 genes, was able to distinguish patients with different outcomes. Only rapidity of response, measured as minimal residual disease (MRD) by flow cytometry, showed a statistically significant impact. Moderate‐intensity therapy, as used in the MLL‐Baby protocol in infants with KMT2A ‐g BCP‐ALL, yields results comparable to other infant studies. Patients with a slow multicolor flow cytometry (MFC)‐MRD response should be subjected to advanced therapies, such as targeted or immunotherapies.